2016
DOI: 10.1080/14686996.2016.1145532
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional printed macroporous polylactic acid/hydroxyapatite composite scaffolds for promoting bone formation in a critical-size rat calvarial defect model

Abstract: We have explored the applicability of printed scaffold by comparing osteogenic ability and biodegradation property of three resorbable biomaterials. A polylactic acid/hydroxyapatite (PLA/HA) composite with a pore size of 500 μm and 60% porosity was fabricated by three-dimensional printing. Three-dimensional printed PLA/HA, β-tricalcium phosphate (β-TCP) and partially demineralized bone matrix (DBM) seeded with bone marrow stromal cells (BMSCs) were evaluated by cell adhesion, proliferation, alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
151
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(167 citation statements)
references
References 61 publications
9
151
1
6
Order By: Relevance
“…Possible changes of PLA properties after gamma‐radiation sterilization were not studied here but the biocompatibility of sterilized PLA printed scaffolds was evaluated. Previous studies showed that PLA degradation releases acidic monomers (lactic acid) that cause inflammation and this property could affect cell attachment and behavior . However, lactic acid is present in the human body and is removed by natural metabolic pathways .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible changes of PLA properties after gamma‐radiation sterilization were not studied here but the biocompatibility of sterilized PLA printed scaffolds was evaluated. Previous studies showed that PLA degradation releases acidic monomers (lactic acid) that cause inflammation and this property could affect cell attachment and behavior . However, lactic acid is present in the human body and is removed by natural metabolic pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been developed for AM such as stereolithography (SLA), selective laser sintering (SLS), three‐dimensional printing (3DP), fused deposition modeling (FDM) for the production of custom, defect‐matched constructs for bone repair . FDM is the most commonly used technique in which the material, a filament, is melted, extruded and deposited to generate a three‐dimensional structure in a layer‐by‐layer fashion with the benefit of controlling both the porosity and the pore size . Another advantage of FDM technology is the ease to associate cells with these thin polymeric scaffolds resulting in a better cell colonization, proliferation and differentiation compared with a larger 3D structure which often includes an inner hypoxic central area, which prevents deep cell colonization.…”
Section: Introductionmentioning
confidence: 99%
“…PCL was the most used polymer as it was found in 29 articles . PLA was used in 13 studies and PLGA in 14 studies . Polyethylene glycol (PEG) was also used in six studies but not as major polymer: it was mixed with PLA, PCL, or with polyoxyethylene terephthalate and polybutylene terephthalate (PEOT/PBT) .…”
Section: Resultsmentioning
confidence: 99%
“…In vivo study of 3D‐printed polylactic acid/HA scaffolds seeded with BMSCs showed they have good osteogenic capability with no difference in inflammation (Fig. B) .…”
Section: Bioprinted Tissuesmentioning
confidence: 99%